2004
DOI: 10.4143/crt.2004.36.2.103
|View full text |Cite
|
Sign up to set email alerts
|

2002 Annual Report of the Korea Central Cancer Registry: Based on Registered Data from 139 Hospitals

Abstract: R esults: O f the total of 99,025 malignancies, 55,398 (55.9% ) cases were males and 43,627 (44.1% ) were fem ales. M ore than one third of cases were from the elderly (65 years old and more). The six leading primary cancer sites in the order of their relative frequency, were stomach (24.0% ), followed by the lung (16.0% ), the liver (15.4% ), the colorectum (11.6% ), the bladder (3.2% ), and the prostate (3.0% ) among males. In females, the breast (16.8% ) was the common cancer site, followed by the stomach (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
111
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(112 citation statements)
references
References 1 publication
0
111
0
1
Order By: Relevance
“…The most commonly administered chemotherapy regimen was gemcitabine/cisplatin (gemcitabine 1000 mg/m 2 Chemotherapy was repeated every 3 weeks. If a response or stable disease was achieved after 2 cycles of chemotherapy, 2-4 additional cycles were administered according to the discretion of the physicians.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly administered chemotherapy regimen was gemcitabine/cisplatin (gemcitabine 1000 mg/m 2 Chemotherapy was repeated every 3 weeks. If a response or stable disease was achieved after 2 cycles of chemotherapy, 2-4 additional cycles were administered according to the discretion of the physicians.…”
Section: Chemotherapymentioning
confidence: 99%
“…Lung cancer is the most common malignancy in many countries, and has become the number one cause of cancer death in Korea, surpassing gastric cancer [1,2]. The majority of lung cancer patients have non-small cell type, which accounts for 80-85% of new cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its decreasing incidence over the past few decades, gastric cancer remains one of the major causes of cancer deaths worldwide (Jemal et al, 2004) and is the most prevalent malignancy in Korea, constituting 24% of all solid tumours in males and 15% in females (Shin et al, 2004). Systemic chemotherapy is often used in patients with locally advanced or metastatic gastric cancer (MGC), but results of most combination regimens have been unsatisfactory, with median survival times of 6 -9 months (Webb et al, 1997;Vanhoefer et al, 2000;Ohtsu et al, 2003).…”
mentioning
confidence: 99%
“…In Korea, HCC accounts for approximately 12.2% of all malignancies, 16.4% in the male population and 6.5% in the female (Shin et al, 2004). Etiological studies have shown that an infection with the hepatitis B or C virus (HBV or HCV) and the ingestion of aflatoxin B1-contaminated food might be important risk factors for HCC (Chen et al, 1977).…”
Section: Introductionmentioning
confidence: 99%